Regional brain structure at the intersection of novelty-seeking trait and anxiety - Georgios Tertikas; Christina N. Kampoureli; Daniel K. Campbell-Meiklejohn; Hugo D. Critchley (Brain Research Bulletin)
The interplay between novelty-seeking (NS) and anxiety is critical in decision-making and adaptive behaviour, yet its neuroanatomical underpinnings remain poorly understood. Given that NS reflects a propensity for exploration and risk-taking, while anxiety modulates threat sensitivity, understanding their interaction may provide insight into neural mechanisms underlying approach-avoidance behaviour. In this study, we investigated the association between regional grey matter (GM) structure, NS, anxiety, and their interaction using voxel-based morphometry (VBM) and source-based morphometry (SBM). Structural MRI data from 50 healthy participants were analysed in relation to NS (Tridimensional Personality Questionnaire) and anxiety (State-Trait Anxiety Inventory). Key findings revealed that NS alone was not associated with GM structure potentially due to more stringent inclusion criteria than previous studies. In contrast, trait anxiety correlated with increased subcallosal gyrus volume in VBM and was negatively associated with SBM-derived components encompassing the temporal and frontal cortices (e.g., left inferior temporal gyrus, inferior frontal gyrus, middle temporal gyrus, left middle frontal gyrus). Importantly, a significant NS-anxiety interaction emerged in the left inferior frontal gyrus (LIFG) GM volume (GMV) in VBM, suggesting a structural basis for the modulation of exploratory behaviour by anxiety. No significant interaction effects were observed in SBM analyses. These findings provide novel insights into the neural correlates of reward-related decision-making and anxiety regulation. The LIFG, in particular, may represent a key region where NS and anxiety converge to shape behaviour. Given its role in impulse control and harm avoidance, these results highlight the potential for targeted interventions aimed at modulating prefrontal circuits in impulsivity-related disorders.